A Survey Research Study about the Impact of Paid Summer Internships on Adolescent Career Self-Efficacy. Issue 2 (4th May 2022) - Merlin-Knoblich, Clare; Brookover, Dana L.; McGee, Juliet
ABSTRACT: Adolescence is a pivotal time for career development, and internship programs are one tool that counselors recommend to clients and students to enhance their career self-efficacy. Despite the supposed value in internships, however, little research has examined the impact such programs have on adolescent interns' career self-efficacy. Research is further scarce on the effect of paid internship programs on adolescents. To fill this gap, we used a retrospective survey research approach to examine a large-scale, paid summer internship program and its impact on adolescents' ( N = 95) Career Self-Efficacy (CSE) and Career Decision Self-Efficacy (CDSE). Participants completed internships in diverse employment fields in which they showed interest. Results showed statistically significant increases in participant CSE and CDSE after their internship experiences, suggesting internships may be a viable method for supporting adolescent career development. Results also indicated that participants' CSE and CDSE did not continue to increase statistically significantly six months after the internships ceased, suggesting that additional programming may be needed to continually enhance adolescent career development. Given the study findings, counselors may benefit from recommending paid summer internships to adolescent clients and students or advocating that such programs be created in their communities.